In a different voice the image of woman in Alicia Tan-Gonzales' Ilongga: Madamu nga Guya - Nava, Ma. Cecilia Locsin (Danyag : Journal of Humanities and Social Sciences, 1999)
Written by Hiligaynon poet, short story writer, novelist, and dramatist Alicia Tan-Gonzales, Ilongga: Madamu nga Guya shows the many facets of the Ilongga as a single woman, wife mother and widow. Drawing from folk forms like luwa, komposo and lullably as well as from traditional and modern poetry, Ilongga: Madamu nga Guya merges Catholic dogma with Western literary tradition, free verse with conventional rhyme and meter to explore woman's relationship with nature, man, and her children. However in dealing with issues like environmental degradation, the damaged goods syndrome, the double-standard, wife battering, marital rape, brain drain, child abuse, commodification of women, and male-female power relations or what Kate Millet calls sexual politics from a woman's point of view, Tan-Gonzales uncovers the workings of patriarchy in the family, society, religion, and the law.